Exploring forensic psychiatric patients’ subjective experiences of whether a social and therapeutic horticulture intervention assists with their recovery from a serious mental illness - Briar, Isabella Ciara (Stellenbosch : Stellenbosch University, 2025)
Thesis (MA)--Stellenbosch University, 2024.